Studies on wound healing potential of polyherbal formulation using in vitro and in vivo assays - Talekar, Yogesh P. (J Ayurveda Integr Med, 2017)
BACKGROUND: The use of herbal plant extracts in wound healing is known through decades, but it is necessary to provide scientific data through reverse pharmacology. OBJECTIVE: The aim of the present study is to find the mechanism behind the healing of wounds using in vitro and in vivo assays. MATERIAL AND METHODS: The study was designed to determine proliferation and mobilization of fibroblast and keratinocytes at the site of injury, angiogenesis at the site of healing and reduction in oxidative stress while healing. In our earlier studies it was observed that herbal extract of Vitex negundo L. (VN), Emblica officinalis Gaertn (EO), and Tridax procumbens L. (TP) showed rapid regeneration of skin, wound contraction and collagen synthesis at the site of injury in excision wound model. In the present study the cell mobilization was monitored in the scratch assay on L929 fibroblastic cell line and HaCaT keratinocytes cell line under the influence of aqueous plant extracts and its formulation. This formulation was also assessed for its angiogenic potential using CAM assay. Study was carried out to probe synergistic effect of polyherbal formulation using excision model in rat. RESULTS: The formulation was found to contain high amount of flavonoids, tannins and phenols which facilitate wound healing. At 20 μg/ml concentration of formulation, significant increase in tertiary and quaternary vessels were observed due to angiogenic potential of formulation. Formulation at the concentration of 3 μg/ml and 5 μg/ml showed significant mobilization of keratinocytes and fibroblasts respectively at the site of injury. Polyherbal formulation showed rapid regeneration of skin and wound contraction. Biochemical parameters like hydroxyproline, hexosamine and collagen turnover was increased in test drug treated animals as compared to untreated, whereas antioxidants such as catalase and GSH were increased significantly and decreased amount of tissue MDA was observed. CONCLUSION: Polyherbal formulation prepared from the plant extracts accelerates wound healing process by proliferation and mobilization of fibroblast and keratinocytes, and angiogenesis at the site of injury. It also shows fast contraction of wound with its beneficial improvement in tissue biochemical and antioxidant parameters.